Influence of terminal branching on the transdermal permeation-enhancing activity in fatty alcohols and acids - Klimentová, Jana; Kosák, Petr; Vávrová, Katerina; Holas, Tomás; Hrabálek, Alexandr (Bioorganic & medicinal chemistry, 2006)
In order to investigate the effect of terminal chain branching in the skin permeation enhancers, seven alcohols and seven acids with the chain length of 8-12 carbons and terminal methyl or ethyl branching were prepared. Their transdermal permeation-enhancing activities were evaluated in vitro using theophylline as a model permeant and porcine skin, and compared to those of the linear standards. Terminal methyl branching increased the enhancing activity only in 12C acid, no effect was seen in the shorter ones. Terminal ethyl however produced a significant increase in activity. In the alcohols, the branching was likely to change the mode of action, due to a different relationship between the activity and the chain length.
Keywords: Permeability; Skin; Swine; mastné alkoholy; Models, Biological; kůže; theofylin; mastné kyseliny; Animals; Fatty Alcohols; Theophylline; permeabilita; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; prasata; Fatty Acids; zvířata; biologické modely